153k views
1 vote
- (2x + 2) - 1 = -x - (x + 3)​

2 Answers

3 votes
Answer: -3 = -3 and infinitely

Explanation:
- (2x + 2) - 1 = -x - (x + 3)​
-2x -2 -1 = -x -x -3
find smaller variable = -2x
subtract it with -2x, -x, & -x

-2 -1 = -3x -3x -3
Find smaller variable, if you say it is both, choose one right or left
I used the right one so -3x +3 with both of them goes to
-2 -1 = -3
-3 = -3 is infinitely
Hope this help
User DisturbedNeo
by
5.7k points
0 votes
ANSWER
Infinite solutions

STEP BY STEP
- ( 2x + 2 ) - 1 = - x - ( x + 3 )
- 2x - 2 - 1 = - x - x - 3
- 2x - 3 = - 2x - 3
infinite solutions
User Ballon
by
5.6k points